(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The importance of the research lies in identifying the most important obstacles facing the implementation of the goals of physical education in accordance with the requirements of sustainable development from the point of view of the supervisors specializing in the Babil Governorate Center. The research problem was: that the curriculum in our country in the past used to focus on preparing students militarily and once on the competitive aspects and other data that led to a lack of focus on aspects that serve the goals that lead to an increase in students’ experiences with modern matters, and the requirements of sustainable development, therefore, the educational curricula, when developed by specialists and defining their objectives, are supposed to serve their interests and the interests of society by focusing on the educational and applied aspects and translating them by those in charge of applying those curricula. As for the research objectives, they were to identify the sustainable development goals related to achieving the goals of physical education for the middle stage from the point of view of supervisors specializing in the central Euphrates governorates, as well as to uncover the obstacles that stand behind the implementation of the goals of physical education in accordance with the requirements of the sustainable development goals and associated with them. The researchers used the descriptive approach using the survey method, and the research community was identified by educational supervisors specializing in physical education in the provinces of the Middle Euphrates (Babil, Najaf, Karbala, Diwaniyah), as their number reached (48) supervisors. Based on the above, the researchers concluded: Most of the obstacles that have been reached are real and realistic, as well as the lack of a culture of practicing sports activities within the groups of Iraqi society, with no conviction among those in charge of the educational process of the necessity and importance of studying physical education. In light of the conclusions, the researchers recommend: Giving great importance to studying physical education in middle schools because of its direct impact on these age groups, while qualifying the teaching staff present in schools in a manner appropriate by entering them in specialized courses in psychological aspects and how to deal with such an important segment Of students.